Markers of Bone Metabolism in Patients With Chronic Pancreatitis and Pancreatic Ductal Adenocarcinoma. Issue 42 (October 2015) - Pezzilli, Raffaele; Melzi d'Eril, Gian Vico; Barassi, Alessandra
Abstract : Abstract: There are no studies comparing some of the most important markers, such as vitamin D, parathormone, osteocalcin, bone alkaline phosphatase, and calcium, in patients with chronic benign and malignant pancreatic diseases. Our objective was to comparatively evaluate serum markers of bone metabolism in patients with chronic pancreatitis and in those with ductal pancreatic adenocarcinoma. Sixty-three consecutive subjects were studied: 30 patients with a firm diagnosis of chronic pancreatitis and 33 having histologically confirmed pancreatic adenocarcinoma. Serum 25-hydroxyvitamin D, bone alkaline phosphatase, osteocalcin, parathormone, and calcium were determined using commercially available kits. Taking into consideration the clinical variables of all 63 patients studied, 25-hydroxyvitamin D was inversely correlated with only the body mass index ( P = 0.007), whereas it was not correlated with age ( P = 0.583) or fecal elastase-1 concentrations ( P = 0.556). Regarding the other substances studied, parathormone was positively correlated with only the age of the patients ( P = 0.015). Of the 5 substances studied, only bone alkaline phosphates were significantly different ( P < 0.001) between patients with chronic pancreatitis and those with pancreatic ductal adenocarcinoma. Within the 2 groups of patients, the 23 patients with chronic pancreatitis without diabetes mellitus had serum concentrations of 25-hydroxyvitamin D significantly lower ( P = 0.045) than those with chronic pancreatitis having diabetes mellitus, whereas smokers with pancreatic ductal adenocarcinoma had serum concentrations of calcium significantly higher ( P < 0.001) as compared to nonsmokers. Altered bone metabolism seems to be associated with chronic diseases of the pancreas; however, the mechanism should be better elucidated.